Seismic stratigraphy and sedimentology of a Miocene carbonate platform in Luconia, South China Sea. (9th August 2020) - Makhankova, Adelya; Sautter, Benjamin; Mathew, Manoj; Menier, David; Poppelreiter, Michael
Abstract : The internal architecture and evolution of isolated carbonate buildups rely on multiple forcing factors, including tectonics and eustatic fluctuations. These parameters control the developmental phases of carbonate buildups such as initiation, growth, and termination stages, and give insights into other morphologic patterns such as backstepping and exposure events. The current study shows the evolution of a Middle Miocene isolated carbonate buildup of Central Luconia in the southern South China Sea, and describes it from large‐scale to very fine detail (km to mm) utilizing newly acquired (2016) 3D seismic data along with core lithofacies and thin sections. The buildup morphology and seismic facies are linked to core facies that can help to uncover the complex development of the carbonate platform. Core‐seismic calibration was used to create maps illustrating carbonate depositional settings for each stratigraphic unit. Here, we identified five seismic units that constitute the main stratigraphic stages of buildup development: (a) initiation as several isolated buildups, (b) coalescence, progradation, and aggradation, (c) aggradation and retrogradation associated with minor backstepping events and major karstification events, (d) retrogradation associated with major backstepping events, and (e) drowning stage. Our results demonstrate that Miocene reefal evolution and buildup architecture in Central Luconia were distinctly affected by diverse endogenic and exogenic processes. The initiation of localized carbonate growth appears to be strongly controlled by the morphology of the pre‐carbonate basement of Central Luconia where the SSW–NNE horst and graben structures were inherited from the poly‐stage opening of the South China Sea during the Early Miocene. Furthermore, sea‐level fluctuations, local and regional tectonic events during the Middle Miocene controlled the rates of accommodation changes, which directly impacted the stratigraphic architecture of the platform. The detailed seismic and sedimentological study documented in this work will benefit the understanding of the paleogeographic and stratigraphic evolution of carbonate buildups in the Luconia region of SE Asia, and in the current and future exploration for substantial conventional resources. Abstract : Luconia platform evolution revealed from its morphology, seismic, and core facies. Palaeo‐tectonic events shaped favourable basement structures for carbonate growth. Global and regional sea‐level variations conditioned platform development. Platform drowning at 8 Ma owing to multiple regional and local controls.